STRATEGI PENGELOLAAN WAKAF TUNAI DI MASJID AGUNG BAITUL MA’MUR KOTA BANGKO KABUPATEN MERANGIN JAMBI - Felly Pratama Putra; Putri Apria Ningsih; Nurfitri Martaliah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to determine the procedure for depositing waqf and knowing the management strategy of cash waqf funds at the Baitul Ma'mur Grand Mosque, Pematang Kandis Village, Bangko District, Merangin Regency. This research is a descriptive qualitative research with observation, interview, and documentation collection techniques, using data analysis techniques in the form of reduction, data presentation, and drawing conclusions. Then the validity of the data is carried out by triangulation. The results showed that 1) The procedure for receiving Waqf at the Baitul Ma'mur Grand Mosque, Pematang Kandis Village, Bangko District, Merangin Regency through buying and selling transactions based on the Qur'an, namely buying and selling between Allah and His servants based on or the basis used in buying and selling at the Baitul Ma'mur Great Mosque is Ali Imron verse 92 and At-Taubah verse 111, the sale made is the type described in the Qur'an as buying and selling between the servants of Allah and Allah which is generally categorized in the form of worship rather than muamalah. 2) Cash Waqf Fund Management Strategy at Baitul Ma'mur Great Mosque Pematang Kandis Village, Bangko District, Merangin Regency with the way of wakif relinquishing ownership of the property that was originally owned, to be used for the benefit of the people/mauquf 'alaih. With the release of the ownership, the waqf property becomes